Simulation of Combustion of Melting Energetic Materials. - Gusachenko, L.K.; Rychkov, A.D. (Defence Science Journal, 2013)
To simulate the combustion of energetic materials (EM) with melting and surface evaporation. a one-dimensional transient model is formulated. In condensed phase, the model considers heat propagation and EMdecomposition via a first order reaction. In the gas phase, it considers heat propagation. species diffusion, exothermic decomposition of vapour via a first order reaction and exothermic conversion of gas components via a second order reaction. The boundary condition at the liquid-gas interface corresponds to equilibrium evaporation described by the Clausius-Clapeyron equation. The effects of melting and exothermicity of condensed phase reaction on the stability of combustion are studied. When simulating radiative ignition, it has been revealed that it can occur in one, two or three stages with different regimes of heat feedback from the gas phase. With relatively slow deradiation, a gas flame approaches the burning surface and sustained combustion is governed by heat feedback from the gas flame with burning rate several times higher than the gasification rate. With fast deradiation at high radiant fluxes the combustion extinguishes, indicating the impossibility of stable ignition under high heating rates. The limitations and possible improvements to the model are considered.